The organization of accounting and public audit in budget organizations (ҚазҰУ хабаршысы. Экономика сериясы, 2017)
This article discusses the procedure for the organization of accounting and public audit in budgetorganizations. Government agencies provide a timely presentation of budget programs administrators,as well as the correctness of the conclusion of the financial plans. Accounting of budgetary organizationsshall be used under the laws of the Republic of Kazakhstan. Particularlly, in the process of puttingthe cost estimates of enterprises, organizations and individuals, as well as a common position and cashsettlements for monitoring the compliance of inventories and government agencies including the completeand accurate information. The objective of public audit is to improve the management and efficientuse of budget funds, the state assets and entities of quasi-public sector organizations.